Impact of Wagering Inducements on the Gambling Behaviors, Cognitions, and Emotions of Online Gamblers: A Randomized Controlled Study - Challet-Bouju, Gaëlle; Grall-Bronnec, Marie; Saillard, Anaïs; Leboucher, Juliette; Donnio, Yann; Péré, Morgane; Caillon, Julie (Frontiers in Psychiatry, 2020)
Wagering inducements are often considered risk factors for gambling problems, but studies exploring the actual impacts of such incentives are scarce. The objective of the present study was to assess the actual impact of wagering inducements on gambling behaviors, cognitions and emotions of online gamblers. One hundred seventy-one adults (18-65 years old) who gamble on a regular basis on the Internet, including at-risk and recreational gamblers, were recruited through media announcements and in panels from survey institutes. Participants were randomly assigned to one of four experimental conditions, in which a defined amount of money was given to the gambler during an experimental gambling session to simulate a wagering inducement (€10, €50, €100 or €200), or the control condition, in which no incentive was given. The experimental gambling session was designed to be as natural as possible (participants gambled with their own gambling account and their own money). Participants completed a pretest interview, took part in the experimental gambling session, and then completed a posttest interview. The impact of wagering inducements was estimated on objective (money wagered and time spent gambling during the gambling session) and subjective (cognitive distortions, enjoyment of gambling, loss of control and respect of usual gambling habits) gambling endpoints that were compared between conditions using ANOVAs. Two-thirds of participants reported having already received wagering inducements at some point of their gambling course. Although no clear effect was demonstrated on objective endpoints, it seems that wagering inducements could lead to extreme expenses, especially for at-risk gamblers. Moreover, inducements increased gambling-related expectancies and perceived loss of control. This research highlighted that wagering inducements may hold risks for certain gamblers, especially at-risk gamblers. It revealed new findings regarding the mechanisms by which inducements may impact gambling behavior, especially through the increase in gambling-related expectancies and perceived loss of control. Preventive measures regarding wagering inducements in the framework of gambling regulations may be useful from a responsible gambling perspective. Future research on the impacts of wagering inducements is still needed, especially more ecological studies based on behavioral tracking data and studies assessing the differential impacts of various incentive types. NCT01789580 (https://clinicaltrials.gov/)